2008
DOI: 10.1088/1367-2630/10/10/103019
|View full text |Cite
|
Sign up to set email alerts
|

High-yield of memory elements from carbon nanotube field-effect transistors with atomic layer deposited gate dielectric

Abstract: Carbon nanotube field-effect transistors (CNT FETs) have been proposed as possible building blocks for future nano-electronics. But a challenge with CNT FETs is that they appear to randomly display varying amounts of hysteresis in their transfer characteristics. The hysteresis is often attributed to charge trapping in the dielectric layer between the nanotube and the gate. This study includes 94 CNT FET samples, providing an unprecedented basis for statistics on the hysteresis seen in five different CNT-gate c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Here palladium was chosen for achieving a low contact resistance between electrodes and the carbon nanotube [21,22]. Also our previous work shows that Pd gives low contact resistance to our SWCNT FETs [14,19].…”
Section: Fabrication and Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here palladium was chosen for achieving a low contact resistance between electrodes and the carbon nanotube [21,22]. Also our previous work shows that Pd gives low contact resistance to our SWCNT FETs [14,19].…”
Section: Fabrication and Measurement Methodsmentioning
confidence: 99%
“…Several studies have shown that by utilizing the hysteresis, CNT FETs can be used as a memory element or sensors [5][6][7][8][9][10][11][12]. Nevertheless, the hysteresis so far has been reported as a more or less random property among the studied CNT FETs [7,9,13] and the challenge still is to be able to control the presence of hysteresis [14].…”
mentioning
confidence: 99%
“…8. A strong hysteresis is seen, with an IorlIofJratio of 10z and a memory window of 4 V. The hysteresis effect of CNTFETs is attributed to absorbed molecules such as water [13] and more recently Rinkio et al have shown that a high-k dielectric gate CNTFET has strong hysteresis due to the charge trapping levels in the high-x dielectric [2]. The results in Fig.…”
Section: R Esults and Discussionmentioning
confidence: 86%
“…The use of a high-x dielectric as a gate insulator for a CNT field-effect transistor (CNTF ET) is of interest because it delivers improved performance due to an increased l orlloffratio. CNTFETs with a HfD z gate dielectric have also recently been researched for application in high-speed CNT memories and a strong hysteresis effect has been observed [2]. CNTs can be introduced onto HfO z using dispersion techniques, but CNT growth by chemical vapor deposition (CYD) would be more compatible with mainstream silicon technology.…”
mentioning
confidence: 99%
“…Other important features of SWCNTs are mechanical strength and high elasticity [21,22]. Those properties determined SWCNTs utilization for applications in rigid [23][24][25] and flexible transparent electronics [26][27][28][29] as well as in optoelectronics [30][31][32]. Transparency, great electrical properties, and inherent nanometer size of SWCNT have motivated the interest to the SWCNT plasmonics.…”
Section: Introductionmentioning
confidence: 99%